Agriculture in Central Asia: current state and development perspectives (Journal of Economic Research & Business Administration, 2021)
This paper aims to analyze the current state and development perspectives of the agricultural sectorof the Central Asian countries. It shows that the sector, despite the decreasing trends in many indicators,plays an important role in terms of production, employment, and trade. The paper also considers tradeindicators of the region with a focus on the pandemic period. It finds that the countries of Central Asiadepend on agricultural imports. However, the Central Asian countries play an important role in the globalagricultural market in terms of wheat and cotton production. The paper identifies major disadvantagesand challenges for regional agriculture, including rising food prices, climate change, quality of institutions,and productivity. It provides recommendations for the regional policymakers, including escapingtrade wars, export bans and other restrictions, and liberalization of trade in agricultural products. In termsof improving the competitiveness of the regional agriculture, the policymakers should focus on climatechange adaptation strategies, stimulate capital investment, and improve institutional quality. These policieswill require both individual and regional efforts of the governments, businesses, and universities ofCentral Asia. The findings and recommendations of the paper can be beneficial for policymakers andscholars of Central Asia.Key words: Central Asia, agriculture, trade, Kazakhstan.